If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 + 2x = -7(8x + 4) + 5x Reorder the terms: 25 + 2x = -7(4 + 8x) + 5x 25 + 2x = (4 * -7 + 8x * -7) + 5x 25 + 2x = (-28 + -56x) + 5x Combine like terms: -56x + 5x = -51x 25 + 2x = -28 + -51x Solving 25 + 2x = -28 + -51x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '51x' to each side of the equation. 25 + 2x + 51x = -28 + -51x + 51x Combine like terms: 2x + 51x = 53x 25 + 53x = -28 + -51x + 51x Combine like terms: -51x + 51x = 0 25 + 53x = -28 + 0 25 + 53x = -28 Add '-25' to each side of the equation. 25 + -25 + 53x = -28 + -25 Combine like terms: 25 + -25 = 0 0 + 53x = -28 + -25 53x = -28 + -25 Combine like terms: -28 + -25 = -53 53x = -53 Divide each side by '53'. x = -1 Simplifying x = -1
| 6x-2=7x-8 | | 9p^2-9=891 | | -38=-4+2n | | 15-7x=x-6-5x | | Y-(8-y)=-20 | | 2a+3=-11 | | 15+8-12=x | | 12x+2=3x+11 | | 16x-18+6x+4=118 | | 32+8v=8(7v-2) | | -8=23-5q | | f(x)=5x^2-7x^3 | | -3-6x^2=-103 | | 1+6p=1-p | | 5+a=29 | | (11t-s)(t+5s)= | | -10x+2=-10 | | -10x+2=-11 | | -12=8+f2 | | 14000=36000-1500t | | 1400=36000-1500t | | -20=-5n+-3n | | 35=1-2a | | -41=2x-7 | | -5(6y-9)-y=-2(y-4) | | 4(x-3)=6(x+1) | | -2(5x-1)=11 | | n^2+5=105 | | -7x+24=8+x | | (2b-5)(2b+5)= | | -3-8(3-2k)=-155 | | -2x^2=-76 |